Pengembangan Media Permainan Biology Racing Game Materi Sistem Pencernaan pada Manusia - TITIS PERMATASARI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
The research background is based on the boredom of the students, the less active students, and students’ difficulties in understanding the matter and the less effective teaching methods to enhance student activity. The use of Biology Racing Game media in the matter of human digestive system hopefully can solve the problems. The purpose of this research is to produce Biology Racing Game media in the matter of human digestive system. This research is a development research using 4D models. However it was done until the development stage. The media was reviewed by a media lecturer, a human anatomy and physiology lecturer and a biology teacher due to the media formats, the appearance of media and validity of concepts. The results show that the media is feasible. Based on the result of the research, Biology Racing Game media of human digestive system is suitable for being used as an understanding concept reinforcement. Keyword: Biology Racing Game, human digestive system.